2004
DOI: 10.1002/mrd.20074
|View full text |Cite
|
Sign up to set email alerts
|

Embryo outcome in Y‐chromosome microdeleted infertile males after ICSI

Abstract: in Y-chromosome microdeletion cycles in which sperm cells were available for intracytoplasmic sperm injection (ICSI), embryo outcome was comparable to conventional IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
0
22
0
2
Order By: Relevance
“…Our study showed no significant differences in embryo implantation, biochemical pregnancy, clinical pregnancy, ectopic pregnancy, delivery, early miscarriage, late miscarriage and ratio of male/female babies in men with or without microdeletion, suggesting that Y chromosome AZFc microdeletion does not affect the outcomes of ICSI treatment. The studies of Patrat et al [33], Kihaile et al [10] and Choi et al [4] have shown similar results. Bellver [34] indicated that Y chromosome AZFc microdeletions do not seem to be related to recurrent spontaneous abortion (RSA) of unknown origin.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Our study showed no significant differences in embryo implantation, biochemical pregnancy, clinical pregnancy, ectopic pregnancy, delivery, early miscarriage, late miscarriage and ratio of male/female babies in men with or without microdeletion, suggesting that Y chromosome AZFc microdeletion does not affect the outcomes of ICSI treatment. The studies of Patrat et al [33], Kihaile et al [10] and Choi et al [4] have shown similar results. Bellver [34] indicated that Y chromosome AZFc microdeletions do not seem to be related to recurrent spontaneous abortion (RSA) of unknown origin.…”
Section: Discussionmentioning
confidence: 53%
“…However, this differs with the report by Oates et al [27] who concluded that sperm production appeared stable over time. Table 6 shows that a have few studies precisely analyzed how Y chromosome microdeletion influences fertilization rate, embryo quality, and pregnancy rates [9,10,12,26,27,33]. Our study showed no significant differences in embryo implantation, biochemical pregnancy, clinical pregnancy, ectopic pregnancy, delivery, early miscarriage, late miscarriage and ratio of male/female babies in men with or without microdeletion, suggesting that Y chromosome AZFc microdeletion does not affect the outcomes of ICSI treatment.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Moreover, about 10% to 15% of idiopathic cases of azoospermia and severe oligozoospermia have microdeletions in AZF regions as the etiologic factor [12][13][14]. The frequency of Y chromosome microdeletions varies between 1% [15] and 55% [16] in the worldwide whereas the few studies performed in Asian male populations showed frequencies of 7.6% to 16.5% in Japan [17][18][19][20][21][22], 11.0% to 19.4% in China [23,24], 10.6% to 11.7% in Taiwan [25,26], 6.4% in Hong Kong [27] and 2.0% to 12.0% in India [12,28,29]. A recently published study reported that the cumulative frequency of Y chromosome microdeletions was 3.5 % in infertile males [30].…”
Section: Abstract Y Chromosome Microdeletion Chromosomal Abnormalitmentioning
confidence: 99%